Na2SO3/NaCO3 PULPING OF SISAL FIBRES: EFFECTS OF ADDITION OF MgCl2 AND SOAKING OF THE FIBRES IN THE COOKING LIQUOR - Katima, J. H.Y.; Halfani, M. R.; Ntalikwa, J. W. (Tanzania Journal of Engineering and Technology, 2018)
Abstract